PERANCANGAN RUANG KOMUNAL PADA HUNIAN MAHASISWA UNTUK PENINGKATAN PEMBELAJARAN DAN KOLABORASI - Widi Dwi Satria; Verza Dillano Gharata; Prayogi Prayogi; Khosyi Mailisa Putri (Jurnal Arsitektur ARCADE, 2024)
Abstract: The existence of communal spaces in the student campus environment is one aspect that must be fulfilled. Currently, students are required to be able to improve learning through collaboration between students. Communal space is a space that can be used together and can be used as a place to gather and interact. This research aims to address the issue of lack of space in student dormitories which has a negative impact on student satisfaction and learning quality. This research proposes to address the issue of lack of open spaces that are useful in the smooth running of student activities by designing communal spaces to support learning and collaboration within the campus environment. The research will involve analysing the needs and preferences of students which includes surveys, in-depth interviews, literature studies as well as incorporating design principles that promote learning and collaboration. The result of this research is a design drawing of a communal space with a circular layout concept that is flexible and adaptive to fulfil the needs of students. Some of the facilities designed include a creativity hallway, reflection room, seating, gazebo, and amphitheatre at the Student Residence of the Sumatra Institute of Technology through 3D designs produced by answering existing design issues. With this design, it is expected to create and improve learning activities and collaboration between students in the student residence environment.Keyword: Design, Communal Space, Residential, Student, CollaborationAbstrak: Keberadaan ruang komunal di lingkungan kampus mahasiswa merupakan salah satu aspek yang harus dipenuhi. Saat ini, mahasiswa dituntut untuk dapat meningkatkan pembelajaran melalui kolaborasi antarmahasiswa. Ruang komunal merupakan ruang yang dapat digunakan bersama dan dapat dimanfaatkan sebagai tempat berkumpul dan berinteraksi. Penelitian ini bertujuan untuk mengatasi masalah minimnya ruang pada asrama mahasiswa yang berdampak negatif pada kepuasan mahasiswa dan kualitas pembelajaran. Penelitian ini mengusulkan untuk menjawab isu minimnya ruang terbuka yang berguna dalam kelancaran kegiatan mahasiswa dengan mendesain ruang komunal guna mendukung pembelajaran dan kolaborasi dalam lingkungan kampus. Penelitian akan melibatkan analisis kebutuhan dan preferensi mahasiswa yang meliputi survei, in-depth interview (wawancara mendalam), studi literatur serta menggabungkan prinsip-prinsip desain yang mempromosikan pembelajaran dan kolaborasi. Hasil dari penelitian ini berupa gambar rancangan ruang komunal dengan konsep circular layout yang bersifat fleksibel dan adaptif bagi pemenuhan kebutuhan mahasisawa. Beberapa fasilitas yang didesain meliputi selasar kreatifitas, ruang refleksi, tempat duduk, gazebo, dan amphitheater pada Hunian Mahasiswa Institut Teknologi Sumatera melalui 3D desain yang dihasilkan dengan menjawab isu perancangan yang ada. DenganÂ  adanya perancangan ini, diharapkan dapat menciptakan dan meningkatkan aktivitas pembelajaran serta kolaborasi antar mahasiswa di lingkungan hunian mahasiswa.Kata Kunci: Perancangan, Ruang Komunal, Hunian, Mahasiswa, Kolaborasi